Thermodynamic characteristics of gas-liquid phase change investigated by lattice Boltzmann method. (5th June 2023) - Huang, Yongfang; Xu, Xiaoxiao; Zhang, Shijie; Wu, Chuang; Liu, Chao; Dang, Chaobin
Highlights: A new way to calculate chemical potential using LB model is proposed. A non-equilibrium thermodynamic analysis method for phase change is developed. The gas-liquid phase change mechanism is revealed with chemical potential. Abstract: The chemical potential is an important thermodynamic parameter during irreversible phase changes. Mass is always transferred from the phase with the higher chemical potential to the lower. The chemical potential can help describe non-equilibrium behavior to reveal phase change mechanism. This paper proposes a method to calculate the chemical potential in the phase change process using the pseudopotential lattice Boltzmann model. It is a new way to understand the phase change mechanism based on the non-equilibrium thermodynamic principle. The results show that the chemical potential varies during the phase change process. In the droplet evaporation process, the chemical potential inside the droplet is higher than that of vapor, and an apparent chemical potential gradient is found at the gas–liquid interface. When the gas superheat increases from 0.09 T s to 0.13 T s, the maximum chemical potential gradient near the phase interface increases by 39%. In the bubble growth process, apparent chemical potential gradients appear at the gas–liquid interface and the nucleation site. The chemical potential gradient at the gas–liquid interface decreases with time. The chemical potential gradient at the nucleation site for the superheat of 0.18 T s is 2.55 times greater than that for the superheat of 0.16 T s . Meanwhile, it is found that the region where the phase change occurs coincides with the region where the chemical potential gradient is large.